Seven Democratic Virtues of Liberal Education A Student-Inspired Agenda for Teaching Civic Virtue in European Universities - Dekker, Teun J. (Routledge Research in Character and Virtue Education, 2023)
This book argues that the liberal arts and sciences (LAS) model of education can inspire reform across higher education to help students acquire crucial civic virtues. Based on interviews with 59 students from LAS programmes across Europe, the book posits that LAS education can develop a range of citizenship skills that are central to the democratic process. The interviews provide insight into how studying LAS prepares students for citizenship by asking them to reflect on their education, what it taught them, and how it did so. Building on these insights, seven key democratic competencies are identified and linked to concrete educational practices that foster them, leading to an agenda for higher education reform. Ultimately arguing for making the teaching of civic virtue a more central part of university education in Europe, this book will appeal to researchers, educators, and politicians with an interest in education policy, philosophy of education, and democratic theory, as well as concerned citizens.